2018
DOI: 10.12691/ajphr-6-4-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Influence Patients in Choosing Their Treating Physicians in the Private Sector in Saudi Arabia

Abstract: Background: Choice of the treating physician by the patient is expected to increase the level of satisfaction and improve health care outcomes. The aim of this study was to explore the factors that may influence patients in choosing their treating physicians in the private health sector in Saudi Arabia. Methods: This was a cross-sectional study. An online questionnaire was distributed targeting Arabic-speaking adults, Saudis and non-Saudis, aged 18 years and above of both genders. The questionnaire included qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Therefore, there is a need to bridge the communication gaps in the physician–patient relationship as a trusting relationship plays a vital role in determining patients’ satisfaction with the healthcare system. [20212223242531]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there is a need to bridge the communication gaps in the physician–patient relationship as a trusting relationship plays a vital role in determining patients’ satisfaction with the healthcare system. [20212223242531]…”
Section: Discussionmentioning
confidence: 99%
“…Acceptance and satisfaction with FPs have also been found to be associated with patients’ trust and desire for meaningful communication. [202122232425] Several studies have found some gaps in the perception of FPs’ roles and responsibilities among patients and their families. [2627] This lack of knowledge may be explained, in part, by patients’ level of awareness of their physicians’ role and poor communication skills from the treating doctor side.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the authors say, that there is an urgent need to understand and develop HPHWs in HRM in such unresponsive institutions so as to achieve benchmarks of service quality in both public and private health/ medical institutions. The healthcare programme in Saudi Arabia is a comprehensive healthcare network through which the country offers quality health coverage involving various government departments for administrative supervision and direction (Al-Jdani et al, BPMJ 27,7 2018;Al-Briek et al, 2018;Abedi et al, 2017;Queiroz et al, 2020). The authors added that the extent of private sector's involvement in providing healthcare services is also growing but many HR-related concerns hamper it.…”
Section: Research Problemmentioning
confidence: 99%